Blood Pressure Intervention and Control in SPRINT. Issue 9 (29th June 2022) - Cushman, William C.; Ringer, Robert J.; Rodriguez, Carlos J.; Evans, Gregory W.; Bates, Jeffrey T.; Cutler, Jeffrey A.; Hawfield, Amret; Kitzman, Dalane W.; Nasrallah, Ilya M.; Oparil, Suzanne; Nord, John; Papademetriou, Vasilios; et al.
Abstract : Background: The SPRINT (Systolic Blood Pressure Intervention Trial) demonstrated reductions in major cardiovascular disease events and mortality with an intensive systolic blood pressure (SBP) goal intervention. However, a detailed description of the blood pressure intervention, antihypertensive medication usage, blood pressure levels, and rates and predictors of blood pressure control has not been reported previously. Methods: Hypertensive participants (n=9361) 50 years and older with elevated cardiovascular disease risk were randomized 1:1 to SBP goal <120 mm Hg or SBP goal <140 mm Hg. Guideline-recommended antihypertensive medications and dosing were provided at no cost. Intensive group participants were started on at least 2 medications, and medications were adjusted monthly until SBP goal was achieved, if feasible. Standard group participants were treated to achieve SBP 135 to 139 mm Hg. Results: Baseline blood pressure (median±interquartile range) was 138±19/78±16 mm Hg. For intensive group participants, percent at goal rose from 8.9% at baseline to 52.4% at 6 months and average antihypertensive medications rose from 2.2 to 2.7; SBP was <120 mm Hg in 61.6% and <130 mm Hg in 80.0% at their final visit. For the standard group participants, percent at goal rose from 53.0% at baseline to 68.6% at 6 months, while antihypertensive medications fell from 1.9 to 1.8. From 6 to 36 months, median SBP was stable at 119±14 mm Hg for intensive and 136±15 mm Hg for standard participants, with stable numbers of medications. Few predictors of SBP control were found in multiple regression models. Conclusions: These results may inform and help replicate the benefits of SPRINT in clinical practice. Registration: URL: http://www.clinicaltrials.gov ; Unique identifier: NCT01206062.